Moral Kerja Guru dalam Mengajardi Sekolah Menengah Atas Negeri Painan - Niki Rahayu (Jurnal Bahana Manajemen Pendidikan, 2013)
This research aims to find out the teacher working in moral teaching at SMA Negeri Painan. This research was descriptive in nature. The population in this research is the teacher SMA Negeri Painan,amounting to 99 people.The amount of samples 51 people. Sample retrieval techniques proportional random sampling.Used instruments questionnaires the Likert scale model has been tested tried and the results invalid and reliability. The Data were analyzed with an average formula. Results of the research in working moral of teachers high in teaching at SMA Negeri Painan. Kata kunci: The teacher working moral